(untitled) (South East Asia Journal of Public Health, 2014)
A stillbirth is a baby born with no signs of life at or after 28 weeks gestation, while preterm births are those which occur between 28 weeks to 32 weeks of gestation. Approximately 3.2 million stillbirths occur annually in low- and middle-income countries. The aim of this paper is to review the present status of the stillbirths and identify the un-derlying factors of stillbirths in India. A search of PubMed and other search engines were conducted to retrieve the literature pertaining to neonatal and perinatal health in India. Four priority areas were used to select the studies: overview (prevalence of the stillbirths), challenges in mapping the potential causes of stillbirths, socio-cultural fac-tors associated with stillbirths, and government response towards stillbirths. It was found that women face many difficulties due to accessibility, availability, affordability and quality issues when utilizing healthcare facilities dur-ing pregnancy. Several studies based on stillbirths also revealed the social aspects of perinatal grief. Stillbirths are bounded by high family pressures and social stigma. A review also revealed that half of all stillbirths occur in India, Pakistan, Nigeria, China and Bangladesh alone. These countries also account for a high number of maternal and newborn deaths. India has highest number of stillbirths in the world the rates range from 20 to 66 per 1000 births in different states. It was also found that healthcare and socio-cultural factors contribute to the increase in the num-ber of stillbirths in India. These issues highlight the need for urgent action and interventions to be taken by the gov-ernment and other organization to improve the situation of stillbirths in India. Early neonatal deaths and stillbirths usually have obstetric causes, and are largely preventable if good quality obstetric care is made available at the right time. Initiatives for strengthening the information management system at the grassroots level to report stillbirths on a regular basis are necessary to improve the neonatal health indicators in India. South East Asia Journal of Public Health 2013; 3(1): 3-9 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17704